Effects of Work Motivation as Variables Intervening Between Autocratic Leadership and Transformational Leadership on Employee Performance in Family Business: (Study at PT. Andalan Medika Sejahtera Abadi) - Aisyah Wida Sari (Universitas Ciputra Surabaya, 2021)
Leadership is an important aspect of an organization or company. The purpose of this study was to measure the effect of work motivation as an intervening variable between autocratic leadership and transformational leadership on employee performance in the family business (study at PT. Andalan Medika Sejahtera Abadi). Respondents in this study were 55 people, all of whom were employees of PT. Andalan Medika Sejahtera Abadi, using quantitative methods and path analysis. In this study, it was found that all variables have a significant and positive effect. However, the relationship between autocratic leadership and motivation has a higher value. The results of this study are unique because they use different subjects from previous studies, namely family business companies.